Pensamento reflexivo e abordagem dos alunos à aprendizagem: uma avaliação sobre o emprego do método de casos de ensino em administração - Silva, Sarah Renata Menezes (2018)
This research aimed to understand the relationship between teaching case methodology, approaches to learning and reflective thinking, as well as the students' perception about learning arising in the subjects of an undergraduate course in Administration. The study starts from the premise that the act of administering is complex, contingent, subject to risks and relative unpredictability, requiring active teaching and learning approaches. To achieve this goal, a study of sequential mixed methods was conducted. The first is a quantitative longitudinal research, and the second is a qualitative research with students from two subjects of the night course of Administration at the Federal University of Ceará. In the quantitative step, the Revised Study Process Questionnaire (R-SPQ-2F), by Biggs, Kember and Leung (2001), and the Reflection Questionnaire (QR), by Kember et al. (2000) with 38 students. The quantitative results rejected the hypotheses that teaching cases favor the deep approach and levels of reflection and critical reflection of reflective thinking. This finding stimulated a complementary step, of qualitative nature, to broaden the understanding of the results of the first stage, through semi-structured interviews and content analysis with 14 students. Qualitative research evidenced that the cases in Administration contribute to the students 'use of the deep approach, despite the influence of certain aspects, such as students' characteristics, academic preference and fatigue, among others. As for the results of reflective thinking, it was concluded that teaching cases seem to discourage habitual action in favor of understanding the concepts. However, the conceptual scope of the cases, in relation to the stage in which the students were in the course, combined with the incipient professional experience of the same ones, were shown as limiting factors for the development of reflection and critical reflection. With regard to learning, it is possible to infer that the cases seem to encourage students to be responsible for the search for alternative sources and active participation, to contribute to the transfer of knowledge among students and to the fixing of learning in the long term.